The Commercial Impact of Sustainable Aviation Fuel Adoption in Commercial Airlines in the United Arab Emirates: An Economic and Industry Analysis - Das, Chandan (International Journal of Research in Interdisciplinary Studies, 2025)
This study examines the commercial impact of Sustainable Aviation Fuel (SAF) adoption by commercial airlines in the United Arab Emirates (UAE). Using a mixed-methods approach combining quantitative economic analysis and qualitative insights from industry reports, the research investigates the economic implications, challenges, and opportunities associated with SAF implementation in the UAE's aviation sector. Findings indicate that while SAF adoption aligns with the UAE's economic diversification and sustainability goals, significant hurdles remain, including high production costs and feedstock availability. The study provides recommendations for policymakers and industry leaders to facilitate successful SAF adoption, contributing to the UAE's position as a global aviation hub while addressing environmental sustainability concerns.